2000
DOI: 10.1002/1521-4095(200011)12:21<1594::aid-adma1594>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Doping in Solution as an Order-Inducing Tool Prior to Film Formation of Regio-Irregular Polyalkylthiophenes

Abstract: Favorable alignment of regio‐irregular poly(3‐alkylthiophene)s in a film can be attained, despite the fact that these polymers lack an intrinsic tendency to form well‐ordered supramolecular aggregates. As reported here, alignment can be achieved simply by oxidizing the polymer in solution prior to film formation. A delicate balance between the degree of order and the level of oxidation in solution is observed. These results point to a way to improve charge transport efficiency, which is influenced by intra‐ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 8 publications
4
48
0
Order By: Relevance
“…Previous studies clearly showed that oxidation can dramatically impact the aggregation of P3ATs and proposed that oxidation transforms the P3HT thienyl backbone from a benzoid to a quinoid structure, increasing the double bond character of the bridges between thienyl rings; This transformation would stiffen the thienyl backbone, strengthening interactions between adjacent chains. 1,23 This idea nicely explains why H 2 SO 4 improves P3HT ordering. However, in these pioneering works P3HT oxidation was extensive, as evidenced by the significant polaron transition bands at wavelengths above 700 nm associated with doping and structural transformation, 1,23 yet in the present study these bands are not seen in the UV−vis spectra of Figure 1b, which means the level of P3HT oxidation is small.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies clearly showed that oxidation can dramatically impact the aggregation of P3ATs and proposed that oxidation transforms the P3HT thienyl backbone from a benzoid to a quinoid structure, increasing the double bond character of the bridges between thienyl rings; This transformation would stiffen the thienyl backbone, strengthening interactions between adjacent chains. 1,23 This idea nicely explains why H 2 SO 4 improves P3HT ordering. However, in these pioneering works P3HT oxidation was extensive, as evidenced by the significant polaron transition bands at wavelengths above 700 nm associated with doping and structural transformation, 1,23 yet in the present study these bands are not seen in the UV−vis spectra of Figure 1b, which means the level of P3HT oxidation is small.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Janssen et al found that regio-irregular poly(3-alkylthiophene), which usually does not form ordered structures, adopts a high degree of order in films made from solution by adding oxidant. 1 And Cho et al promoted the formation of P3HT nanocrystals from solution using HAuCl 4 , a procedure that improves the field-effect mobility of P3HT films by 2 orders of magnitude. 23 The oxidant heavily dopes the dissolved P3HT molecules and causes their structural transformation, as manifested in ∼700−1100 nm bands in the UV− vis absorption spectra attributed to polaron transition.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is postulated that the transition to the higher symmetry cubic phase in the p-doped polymer may arise from a combination of preferential solvation of the polyalkylthiophene backbone and the formation of the partial quinoid geometry (increased double bond character of the thiophene inter-ring) of the thiophene upon oxidation, a state which has been previously believed to reduce conformational disorder. 33 Electronic Transport. The conductivity for the as-synthesized polymer was determined to be 4.7 × 10 -7 S/cm.…”
Section: Resultsmentioning
confidence: 99%
“…[8,11,13,21] Among the factors affecting field-effect mobility, the molecular ordering of nanocrystallites in thin films of regioregular P3HT has been the most extensively investigated. In order to enhance two-dimensional molecular ordering, many groups have examined the outcomes of modifying the molecular parameters (regioregularity, [13,22] molecular weight, [23] and sidechain length [24] ) and processing conditions (solvent power, [8] film thickness, [25] doping level, [26] and film-forming method [27] ). Despite the resulting improvements in the field-effect mobility of regioregular P3HT, little is yet known about how the interWith the aim of enhancing the field-effect mobility by promoting surface-mediated two-dimensional molecular ordering in self-aligned regioregular poly(3-hexylthiophene) (P3HT) we have controlled the intermolecular interaction at the interface between P3HT and the insulator substrate by using self-assembled monolayers (SAMs) functionalized with various groups (±NH 2 , ±OH, and ±CH 3 ).…”
Section: Introductionmentioning
confidence: 99%